If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -1(3 + -1x) + 5) = 0 4(2x + (3 * -1 + -1x * -1) + 5) = 0 4(2x + (-3 + 1x) + 5) = 0 Reorder the terms: 4(-3 + 5 + 2x + 1x) = 0 Combine like terms: -3 + 5 = 2 4(2 + 2x + 1x) = 0 Combine like terms: 2x + 1x = 3x 4(2 + 3x) = 0 (2 * 4 + 3x * 4) = 0 (8 + 12x) = 0 Solving 8 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 12x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 12x = 0 + -8 12x = 0 + -8 Combine like terms: 0 + -8 = -8 12x = -8 Divide each side by '12'. x = -0.6666666667 Simplifying x = -0.6666666667
| 3x-12=-2x+11 | | 8j+2j-5j+3j-6j=20 | | 11w-10w-1=14 | | -11z-(-5z)-(-9z)-(-4)=-17 | | 3c+2c+4=14 | | 9+7p=6p | | 4j+j+4j-4j-3j=10 | | -2g-3g-(-10g)+13g+(-5g)=-13 | | 16h+(-14h)+(-3h)=9 | | 3x^2(6x)= | | 18v-15v-v-v=19 | | 10w-5w=20 | | 20b-14b=18 | | 2m+7m=9 | | 9x+n=x^2 | | 4(k+4)=20 | | -22+3x-(-2)=-2x | | 3(j-5)+1=10 | | 2/s=1 | | 2(d-13)-11=1 | | 2n^2=-n+3 | | j-2/2=2 | | 15/x=.55 | | 4/d=2 | | 7+9g=25 | | -42=q/6-47 | | c(c-7)=0 | | 13=g/3-(-11) | | 0=25-10x^2 | | -3+(-n)=-7 | | x^2-4x+9=2 | | 3x^2+40x-2000=0 |